Educação alimentar e nutricional na escola: uma ação normativa ou problematizadora? - Kátia Cilene de Almeida (2019)
The Food and Nutrition Education actions are historically characterized by the distribution of food and the promotion of healthy eating practices. One of the spaces in which the promotion of healthy eating practices can occur is the school. In this sense, the school enables the promotion of health in the exercise of rights and duties and stimulates healthy behaviors and attitudes. This research aims to identify the pedagogical foundations present in the actions of Food and Nutrition Education developed in public schools in the municipality of Belo Horizonte and indicates a proposal for the teaching of science on the theme of food in the early years of elementary education. The research methodology used is qualitative, approach which was based on literature review of school meals in Brazil and studies the proposals of Food and Nutrition Education under the National School Feeding Program and the Food and Nutrition Education Program of the municipality of Belo Horizonte. For data analysis and interpretation, the content analysis technique was used with the theoretical-methodological support Bardin (2016) and Minayo (2002).The readings of the Food and Nutrition Education Program and the principles that guide the practices of Food and Nutrition Education allowed the construction of five categories of analysis considering the following aspects: 1) nutritional; 2) food; 3) cultural; 4) ecological: diversity and sustainability; 5) educational mentioned in the program. The survey results indicated the absence of the pedagogical foundations in the program actions, indicating the importance of a wide discussion about this theme and its insertion in the program. For the construction of the teaching proposal were used as reference theorists Paulo Freire and Vygotsky education; The educator’s guide: promoting food and nutrition education in schools(2013), the food guide for the Brazilian population (2014) and the food security guide(2015). This research is expected to provide teachers with knowledge about the trajectory of food and nutrition education in Brazil, specifically in the city of Belo Horizonte. It also contributes to the aspects of food as a Public Policy, spreading and disseminating information for the development of meaningful and reflective activities on this subject with the students.